The European Union in the twenty-first century : major political, economic and security policy trends - Günar, Altuǧ; Saygin, Didem (Emerald Publishing Limited, 2023)
The European Union in the Twenty-First Century: Major Political, Economic and Security Policy Trends unpacks some of the most prominent issues faced by the EU over the last two decades and considers how they may shape its future, as well as the future of international politics. Altug Günar, Didem Saygin and other leading experts analyse some of the biggest challenges for European politics and society since the start of the millennium, including Brexit, the 2008 financial crisis, the rise of far-right anti-immigration parties, and the political and economic dimensions of the Covid-19 pandemic. Chapters also explore the impact of EU policy beyond its continental bounds by analysing its external relations with China, Russia, Turkey, Ukraine, and ACP countries. With expert analyses and a multidisciplinary approach to issues not yet widely broached in EU political scholarship, The European Union in the Twenty-First Century: Major Political, Economic and Security Policy Trends critically examines the most pressing issues of the past two decades to consider how the future of the European Union has been and will be shaped in response.